MODEL PEMBELAJARAN BERBASIS PROYEK PADA EKSTRAKURIKULER SENI TARI DALAM MENGUKIR PRESTASI DI SMP PGRI 1 BUDURAN SIDOARJO - natasya dwi amalia putri; Warih Handayaningrum (Universitas Negeri Surabaya, 2025)
Extracurricular learning serves as an important medium for developing students' potential beyond formal classroom instruction. In dance education, extracurricular activities are designed not only to improve students' technical dance skills but also to foster creativity, critical thinking, collaboration, responsibility, and self-confidence. One instructional model considered effective in achieving these objectives is Project-Based Learning (PjBL), which emphasizes student-centered learning through the completion of meaningful projects that produce authentic products. This study aims to describe the implementation of the Project-Based Learning model in dance extracurricular activities at SMP PGRI 1 Buduran Sidoarjo and to examine its contribution to students' achievements. The research employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation involving the principal, extracurricular coordinator, dance instructor, and participating students. Data analysis consisted of data reduction, data display, and conclusion drawing, while source and technique triangulation were employed to ensure data validity. The findings reveal that Project-Based Learning was implemented through six systematic stages: project identification, project planning, scheduling, project implementation under teacher supervision, presentation of project outcomes, and evaluation of both learning processes and products. This approach produced several dance performances, including the creation of Tari Prasung Suran for the National Student Arts Festival and Competition (FLS3N). Furthermore, the implementation of PjBL enhanced students' cognitive, affective, and psychomotor competencies, as reflected in improved theoretical understanding, dance performance skills, teamwork, discipline, and confidence during performances and competitions.